2015
DOI: 10.1002/tox.22199
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-rich diesel exhaust-induced liver damage via inhibited transactivation of peroxisome proliferator-activated receptor alpha

Abstract: Diesel exhaust emission contains a high amount of nano-sized particles and is considered to be systemically distributed in the body. However, few studies about the effects of nanoparticle rich-diesel exhaust (NR-DE) on liver have been reported. The present investigation focuses on the effects of NR-DE on livers in rats, especially concerning inflammation and lipid metabolism. Male F344 rats were exposed to fresh air or low (24 ± 7 µg/m ), medium (39 ± 4 µg/m ) and high (138 ± 20 µg/m ) concentrations of NR-DE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…1B) activities respectively,when compared to control. The data also showed that pretreatment with aqueous rooibos extract significantly (p<0.001) caused a 1.55-and 1.42-fold decrease in serum AST and ALT activities when compared to DEP exposure only ( Fig.1A & B), Exposure of rats to nanoparticle rich-diesel exhaust has been reported to increase serum ALT and AST activities (Ito et al, 2016). The present study was in agreement with this earlier study.…”
Section: Resultssupporting
confidence: 92%
“…1B) activities respectively,when compared to control. The data also showed that pretreatment with aqueous rooibos extract significantly (p<0.001) caused a 1.55-and 1.42-fold decrease in serum AST and ALT activities when compared to DEP exposure only ( Fig.1A & B), Exposure of rats to nanoparticle rich-diesel exhaust has been reported to increase serum ALT and AST activities (Ito et al, 2016). The present study was in agreement with this earlier study.…”
Section: Resultssupporting
confidence: 92%
“…PM is a complex mixture of solid and/or liquid organic and inorganic substances suspended in the atmosphere and comprises many different types of particle depending on the emission source (e.g., natural or industrial), including diesel exhaust particles (DEP), residual oil fly ash, and urban air particles [1]. Epidemiological and toxicological studies have shown that exposure to PM can induce and exacerbate clinical manifestations of lung [2], liver [3], kidney [4], and heart [5] diseases. In particular, PM with an aerodynamic diameter < 2.5 μ m (i.e., PM2.5 or fine particles) can affect the human respiratory and circulatory systems, since small particles can travel deep into the respiratory tract, carrying toxic compounds into lung alveoli and blood vessels or capillaries [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in this study, we analyzed the PAHs and OC/EC ratios in APM and DEP. PAHs and OC/EC ratios are associated with the induction and exacerbation of lung diseases [8][9][10][11][12][13][14][15] . Our results showed that PAH levels were higher in APM than in DEP, and the OC/EC ratio was similar between DEP and APM (Fig.…”
Section: Discussionmentioning
confidence: 99%